Motivations and Experiences of Whitewater Rafting Tourists on the Ocoee River, USA. (23rd January 2017) - Beckman, Eric; Whaley, Jeremy E.; Kim, Youn‐Kyung
Abstract: This study explored the relationships that adventure motivations have with adventure experiences (i.e. emotional response and place attachment) and behavioral outcomes (i.e. revisit intention and word‐of‐mouth). Based on 690 surveys collected from whitewater rafters at the Ocoee River in Tennessee, structural equation modeling revealed that thrill and nature motivations led to a positive affective response towards the adventure activity, which led to an attachment to the adventure destination and positive behavioral outcomes and that perceived risk was a significant moderator between thrill and affective response. These findings will assist marketers in promoting the activities and locations to attract more adventure tourists. Copyright © 2017 John Wiley & Sons, Ltd.